2021
DOI: 10.3390/insects12050432
|View full text |Cite
|
Sign up to set email alerts
|

Insects’ Production, Consumption, Policy, and Sustainability: What Have We Learned from the Indigenous Knowledge Systems?

Abstract: Edible insects can be produced sustainably, with less environmental impact than other forms of livestock. Globally, over 2000 edible insect species have been reported and are regarded as a great source of nutrition, both as food and feed. Over the years, rural people have used indigenous knowledge to either store or process such insects. However, such valuable knowledge, if not properly recorded and documented, can easily be lost. Thus, there is a need to strike a balance between the use of indigenous and scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 93 publications
(124 reference statements)
0
15
0
2
Order By: Relevance
“…The lack of clear legislation and regulatory guidelines governing trading and insect use as food in South Africa might be the primary barrier that prevents local authorities from including edible insects in rural economic development plans [44]. In addition, the lack of legislation and regulatory guidelines that recognise and govern the edible insect sector as part of agricultural activity is concerning [49]. There are no clear guidelines on the use of insects as food in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of clear legislation and regulatory guidelines governing trading and insect use as food in South Africa might be the primary barrier that prevents local authorities from including edible insects in rural economic development plans [44]. In addition, the lack of legislation and regulatory guidelines that recognise and govern the edible insect sector as part of agricultural activity is concerning [49]. There are no clear guidelines on the use of insects as food in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Edible insects have been shown to have nutritional, ecological and economic advantages, and increased insect farming is considered to promote increased food security across the world. Insect products are also considered to be beneficial for the health and welfare of livestock and they could lead to reduced antibiotic use in livestock production [25].…”
Section: The Benefits Of Breeding Insectsmentioning
confidence: 99%
“…They are high in amino acids and monosatured fatty acids, which meets the requirements of humans. Besides being high in nutrients, edible insects are also rich in certain vitamins and minerals [25] and have a high content of fiber compared to livestock, as seen in Table 1 [26,27]. It has also been reported that insect protein has as many nutritional benefits as milk proteins [28] and that edible insects might decrease cholesterol levels in humans by 60% [29].…”
Section: The Benefits Of Breeding Insectsmentioning
confidence: 99%
See 2 more Smart Citations